การพัฒนาตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชา - คอนจอหอ, พรรณี; บุรีภักดี, เฉลียว; พงศ์ติยะไพบูลย์, สุมาลี; กลิ่นงาม, เสนาะ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) พัฒนาตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชา 2) ประเมินการยอมรับตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชา กลุ่มตัวอย่างประกอบด้วยนักศึกษามหาวิทยาลัยราชภัฏเพชรบุรีที่กำลังศึกษาอยู่ชั้นปีที่ 2 ภาคการศึกษาที่ 2/2561 จำนวน 155 คน โดยวิธีเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย ประกอบด้วย ตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชาและแบบประเมินการยอมรับตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชา สถิติที่ใช้ในการวิเคราะห์ข้อมูลประกอบด้วย ค่าเฉลี่ย () ค่าเบี่ยงเบนมาตรฐาน (S.D.) ผลการวิจัยพบว่า 1) ตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชาประกอบด้วยองค์ประกอบหลัก 4 ด้านคือ (1) ความคิดพื้นฐานเกี่ยวกับชีวิตอนาคต (2) คุณลักษณะความมุ่งผลสัมฤทธิ์สูงในการเรียนและการทำงาน (3) คุณลักษณะการมีความมุ่งมั่นตั้งใจเรียน เพื่อให้ได้เกรด A ในรายวิชาที่เรียน 1 รายวิชา และ (4) ทักษะการวางแผนพัฒนาการเรียน เพื่อให้ได้เกรด A ในรายวิชาที่กำหนด 2) นักศึกษายอมรับตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอนรายวิชาที่สามารถเปลี่ยนแปลงคุณลักษณะในตัวผู้เรียนด้วยตนเองในระดับมากที่สุดทุกรายการ 4 ด้าน คือ (1) ด้านความคิดพื้นฐานเกี่ยวกับชีวิตอนาคต (2) ด้านคุณลักษณะความมุ่งผลสัมฤทธิ์สูงในการเรียนและการทํางาน (3) ด้านคุณลักษณะการมีความมุ่งมั่นตั้งใจเรียนเพื่อให้ได้เกรด A ในรายวิชาที่กําหนด 1 รายวิชา (4) ด้านการวางแผนพัฒนาการเรียนเพื่อให้ได้เกรด A ในรายวิชาที่กําหนด คำสำคัญ : ตัวแบบยกระดับผลสัมฤทธิ์การเรียนการสอน ABSTRACT The purposes of this study were 1) to develop a model raises the level of achievement in teaching and learning and 2) to evaluate the acceptance of the model raises the achievement in teaching and learning. The target group consisted of 155 sophomore students in Semester 2/2561 at Phetchaburi Rajabhat University obtained by a purposive sampling. The tools used in this study were the model raises the level of achievement in teaching and learning and an evaluation form of the model raises the level of achievement in teaching and learning. Statistics used in data analysis included mean () and standard deviation (S.D.). The result of this research indicated that the 1) model raises the level of achievement in teaching and learning included four main elements which were (1) basic ideas about future life (2) high achievement characteristics in learning and working (3) a commitment to study to earn an A in a course of study one course (4) learning development pattern to earn an A in a desired course of study. 2) Students also accepted that the model allowed student to change the characteristics of the students themselves in four elements the most every item as follow:(1) The basic ideas of life in the future(2) The high achievement characteristics in learning and working was slightly increased. (3) The commitment to study to earn an A in a course of study one course was greatly increased. (4) Lastly, the learning development pattern to earn an A in a desired course of study was greatly increased. Keywords: Achievement Model, Teaching and Learning